Design of a QA method to characterize submillimeter-sized PBS beam properties using a 2D ionization chamber array. (15th May 2018) - Lin, Yuting; Bentefour, Hassan; Flanz, Jacob; Kooy, Hanne; Clasie, Benjamin
Abstract: Pencil beam scanning (PBS) periodic quality assurance (QA) programs ensure the beam delivered to patients is within technical specifications. Two critical specifications for PBS delivery are the beam width and position. The aim of this study is to investigate whether a 2D ionization chamber array, such as the MatriXX detector (IBA Dosimetry, Schwarzenbruck, Germany), can be used to characterize submillimeter-sized PBS beam properties. The motivation is to use standard equipment, which may have pixel spacing coarser than the pencil beam size, and simplify QA workflow. The MatriXX pixels are cylindrical in shape with 4.5 mm diameter and are spaced 7.62 mm from center to center. Two major effects limit the ability of using the MatriXX to measure the spot position and width accurately. The first effect is that too few pixels sample the Gaussian shaped pencil beam profile and the second effect is volume averaging of the Gaussian profile over the pixel sensitive volumes. We designed a method that overcomes both limitations and hence enables the use of the MatriXX to characterize sub-millimeter-sized PBS beam properties. This method uses a cross-like irradiation pattern that is designed to increase the number of sampling data points and a modified Gaussian fitting technique to correct for volume averaging effects. Detector signals were calculated in this study and random noise and setup errors were added to simulate measured data. With the techniques developed in this work, the MatriXX detector can be used to characterize the position and width of sub-millimeter, σ   =  0.7 mm, sized pencil beams with uncertainty better than 3% relative to σ . With the irradiation only covering 60% of the MatriXX, the position and width of σ   =  0.9 mm sized pencil beams can be determined with uncertainty better than 3% relative to σ . If one were to not use a cross-like irradiation pattern, then the position and width of σ   =  3.6 mm sized pencil beams can be determined with uncertainty better than 3% relative to σ . If one were to not use a cross-like pattern nor volume averaging corrections, then the position and width of σ   =  5.0 mm sized pencil beams can be determined with uncertainty better than 3% relative to σ . This work helps to simplify periodic QA in proton therapy because more routinely used ionization chamber arrays can be used to characterize narrow pencil beam properties.